EXPLORATION AND COLLECTING OF WILD LACTUCA L. SPECIES, VEGETABLE AND CUCURBIT CROP GENETIC RESOURCES IN PRIMORSKY AND KHABAROVSK REGIONS OF THE RUSSIAN FEDERATION IN 2017 - A. B. Kurina; D. L. Kornyukhin; P. A. Chebukin (Труды по прикладной ботанике, генетике и селекции)
A collecting mission was carried out over the territory of Primorsky and Khabarovsk Regions in 2017. The goal of this mission was searching for wild species of the genus Lactuca L., and collecting samples of those species. Also, collecting of vegetable crops and cucurbits as well as wild relatives of such crops was important. Finally, 453 wild samples belonging to 8 species of Lactuca L., were collected in their native habitats. In the explored area, Lactuca spp. were found growing almost everywhere, but each species had its own preferable ecotype. The dataset of all collecting spots of the gathered Lactuca species including geographical coordinates of each point was developed. Besides, 243 samples of vegetable crops and cucurbits were purchased at the local markets, and 94 samples of crops wild relatives were collected in wild nature.